KEMAMPUAN PROBLEM POSING SISWA PADA MATERI ARITMATIKA SOSIAL DI KELAS VIII SMPN 8 PONTIANAK - Wilyan, Sazha; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is to find out the students problem posing ability on social arithmetic material in class VIII Junior High School 8 Pontianak. This study used descriptive qualitative method. Data collected using tests, interviews, and documentation. The subjects of this study were 6 out of 25 students of class VIII E Junior High School 8 Pontianak representing the answers of other students. The test results show that the ability of students to make questions about social arithmetic is good, this can be seen from the work of students who are able to make story questions based on images presented to him as much as 66.6% of 6 students and the ability of students to solve questions about social arithmetic is good, this can be seen from the work of students who are able to solve the problem stories made by as much as 50% of 6 students.   Keywords: Problem posing, Social Arithmetic